219k views
4 votes
Solve the system of equations.

\begin{aligned} &-6y+11x = -36 \\\\ &-4y+7x=-24 \end{aligned}


−6y+11x=−36
−4y+7x=−24


User Furicle
by
5.9k points

1 Answer

4 votes

Answer:

The solutions to the system of equations will be:


y=6,\:x=0

Explanation:

Given the equation


-6y+11x=-36


-4y+7x=-24

solving the system of equations


\begin{bmatrix}-6y+11x=-36\\ -4y+7x=-24\end{bmatrix}


\mathrm{Multiply\:}-6y+11x=-36\mathrm{\:by\:}2\:\mathrm{:}\:\quad \:-12y+22x=-72


\mathrm{Multiply\:}-4y+7x=-24\mathrm{\:by\:}3\:\mathrm{:}\:\quad \:-12y+21x=-72


\begin{bmatrix}-12y+22x=-72\\ -12y+21x=-72\end{bmatrix}


-12y+21x=-72


-


\underline{-12y+22x=-72}


-x=0


\begin{bmatrix}-12y+22x=-72\\ -x=0\end{bmatrix}

solving for x


-x=0


\mathrm{Divide\:both\:sides\:by\:}-1


(-x)/(-1)=(0)/(-1)


x=0


\mathrm{For\:}-12y+22x=-72\mathrm{\:plug\:in\:}x=0


-12y+22\cdot \:0=-72


-12y+0=-72


-12y=-72


\mathrm{Divide\:both\:sides\:by\:}-12


(-12y)/(-12)=(-72)/(-12)


y=6

Therefore, the solutions to the system of equations will be:


y=6,\:x=0

User John Nyingi
by
6.0k points